Acclimation and stress response of Prochlorococcus to low salinity - He, Xiayu; Liu, Huan; Long, Lijuan; Dong, Junde; Huang, Sijun (Frontiers in Microbiology, 2022)
Prochlorococcus is an obligate marine microorganism and the dominant autotroph in tropical and subtropical open ocean. However, the salinity range for growing and response to low salinity exposure of Prochlorococcus are still unknown. In this study, we found that low-light adapted Prochlorococcus stain NATL1A and high-light adapted strain MED4 could be acclimated in the lowest salinity of 25 and 28 psu, respectively. Analysis of the effective quantum yield of PSII photochemistry (Fv/Fm) indicated that both strains were stressed when growing in salinity lower than 34 psu. We then compared the global transcriptome of low salinity (28 psu) acclimated cells and cells growing in normal seawater salinity (34 psu). The transcriptomic responses of NATL1A and MED4 were approximately different, with more differentially expressed genes in NATL1A (525 genes) than in MED4 (277 genes). To cope with low salinity, NATL1A down-regulated the transcript of genes involved in translation, ribosomal structure and biogenesis and ATP-production, and up-regulated photosynthesis-related genes, while MED4 regulated these genes in an opposite way. In addition, both strains up-regulated an iron ABC transporter gene, idiA, suggesting low salinity acclimated cells could be iron limited. This study demonstrated the growing salinity range of Prochlorococcus cells and their global gene expression changes due to low salinity stress.